Bauran Promosi Produk Kopi - Fahri Fauzi; Anne Ratnasari (UNISBA Press, 2023)
Abstract. A Y A . K O P I is one of the coffee shops in Bandung, located on Jl. Gegerkalong Hilir no. 47. This coffee shop provides a variety of processed coffee and non-coffee menus, also various kinds of snacks. The purpose of this study is to find out how to implement promotional activities which contain several elements of the promotional mix, including advertisement for instagram ads, sales promotion by providing discounted prices on several menus, and organizing Movie Night events which are the mainstay of the promotional activities. The focus point of this research is “How is the promotion mix of A Y A . K O P I?” This study uses a qualitative method with a case study approach. Data collection techniques were applied using interviews, observations, documentations, and literature study. This study also uses the triangulation of sources and informants, which are the general manager, social media officer, and customer The results of this study indicated 1) The advertisements presented are advertisements about the products and the atmosphere of the place, ongoing promotions, and informations on the events that are being held. 2) The sales promotion given by this coffee shop is giving discounts and special prices for large portions of products. 3) The Movie Night events are the mainstay in the promotional activities because mostly consumers feel they can get a new experience and the events are different from any events held by other coffee shops. Abstrak. AYA . K O P I adalah salah satu kedai kopi di Bandung yang berlokasi di Jl. Gegerkalong Hilir no. 47. Warung kopi ini menyediakan berbagai menu olahan kopi dan non kopi, juga berbagai macam makanan ringan. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pelaksanaan kegiatan promosi yang mengandung beberapa unsur bauran promosi antara lain iklan untuk instagram ads, promosi penjualan dengan memberikan potongan harga pada beberapa menu, dan menyelenggarakan acara Movie Night yang menjadi andalan dari aktivitas promosi. Titik fokus penelitian ini adalah “Bagaimana bauran promosi A Y A . KOP I?” Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan dengan wawancara, observasi, dokumentasi, dan studi pustaka. Penelitian ini juga menggunakan triangulasi narasumber dan informan yaitu general manager, social media officer, dan pelanggan. Hasil penelitian ini menunjukkan 1) Iklan yang disajikan adalah iklan tentang produk dan suasana tempat, promosi yang sedang berlangsung, dan informasi tentang acara yang sedang diadakan. 2) Promosi penjualan yang diberikan kedai kopi ini adalah memberikan potongan harga dan harga khusus untuk produk dalam porsi besar. 3) Acara Movie Night menjadi andalan dalam kegiatan promosi karena sebagian besar konsumen merasa bisa mendapatkan pengalaman baru dan acara tersebut berbeda dengan acara yang diadakan oleh kedai kopi lainnya.